Do the provisions of section 3(7)(a)(ii) read with section 3(7)(b)(i) of the Admiralty Jurisdiction Regulation Act 105 of 1983 infringe the substantive requirements of section 25(1) of the Constitution of the Republic of South Africa Act 108 of 1996? - Doble, Vanessa (Shipping Law Unit, 2015)
In this dissertation, the issue that is considered is whether or not the provisions of section 3(7)(a)(ii) read with section 3(7)(b)(i) of the Admiralty Jurisdiction Regulation Act 105 of 1983 ('the Act') constitute an arbitrary deprivation of a minority shareholder's property because they permit the deprivation of minority shareholder's property interests purely on the basis of common control by the majority shareholder.